The Roles of Cytoplasmic Polyadenylation Element Binding Protein 1 in Tumorigenesis - Li, JiaYi; Wu, Yinxin; Zhang, Dingyin; Zhang, Ziyan; Li, Songqiang; Cheng, Xi; Chen, Lihan; Zhou, Gang; Yuan, Chengfu (Mini Reviews in Medicinal Chemistry, 2024)
BackgroundCPEB1 is an alternative polyadenylation binding protein that promotes or suppresses the expression of related mRNAs and proteins by binding to a highly conserved Cytoplasmic Polyadenylation Element (CPE) in the mRNAs 3’UTR. It is found to express abnormally in multiple tumors and affect tumorigenesis through many pathways. This review summarizes the functions and mechanisms of CPEB1 in a variety of cancers and suggests new directions for future related treatments.MethodsA total of 95 articles were eligible for inclusion based on the year, quality of the research, and the strength of association with CPEB1. In this review, current research about how CPEB1 affects the initiation and progression of glioblastoma, breast cancer, hepatocellular carcinoma, gastric cancer, colorectal cancer, non-small cell lung cancer, prostate cancer, and melanoma are dissected, and the biomedical functions and mechanisms are summarized.ResultsCPEB1 mostly presents as a tumor suppressor for breast cancer, endometrial carcinoma, hepatocellular carcinoma, non-small cell lung cancer, prostate cancer, and melanoma. However, for glioblastoma, gastric cancer, and colorectal cancer, CPEB1 exhibts two opposing properties of tumorigenesis, either promoting or inhibiting it.ConclusionCPEB1 is likely to serve as a target and dynamic detection index or prognostic indicator for its function of apoptosis, activity, proliferation, migration, invasion, stemness, drug resistance, and even ferroptosis in various cancers.
Keywords: cancers